Mechanics and Analysis of Advanced Materials and Structures - Yoshida, Sanichiro; Pappalettera, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Modern materials and structures are significantly different from conventional ones. Their sizes can be orders of magnitude smaller, and their compositions are so sophisticated that traditional characteristic methods are inapplicable. Non-conventional methods are essential to tackle these issues, which must often be approached in an interdisciplinary fashion. This Special Issue is a collection of articles that shed light on these problems.